Facehunter - Rodic, Yvan (London : Thames & Hudson, 2010)
Face Hunter travels the globe, snapping the most stylish looks in the street and discovering beguiling individualists in some 30 countries. This book features over 300 photographs, accompanied by Hunter's observations from the frontline of fashion: the street corner.
boek